Pengaruh Karakteristik Individu terhadap Kinerja Pegawai yang di Mediasi oleh Motivasi Kerja Pegawai pada RSUD KH. Arif Daud Kuala Tungkal - Azizah Azizah; Khuluqon Azima (Universitas Batanghari Jambi, 2021)
The purpose of this study was to analyze the effect of individual characteristics of employees on employee performance either directly or indirectly through employee motivation. The target population in this study were non-medical employees at the Regional General Hospital (RSUD) KH. Arif Daud Kuala Tungkal, Tanjung Jabung Barat Regency, as many as 54 employees. Because the population in this study is less than 100, the sampling technique in this study uses saturated sampling, where all the populations in this study were used as research samples. The approach in this study uses a quantitative approach with survey methods and is analyzed using Path Analysis. The results of this study conclude several points, namely: 1) individual characteristics have a significant effect on employee work motivation; 2) individual characteristics have a significant effect on employee performance; 3) work motivation has a significant effect on employee performance; and 4) motivation is not able to mediate individual characteristics on employee performance.